Leaf Coloration in Acer palmatum Is Associated with a Positive Regulator ApMYB1 with Potential for Breeding Color-Leafed Plants - Sujing Sun; Qiang Zhang; Yongfan Yu; Jianyuan Feng; Changlai Liu; Jiading Yang (Plants, 2022)
Anthocyanin biosynthesis and accumulation is closely associated with tissue/organ coloring in plants. To gain insight into the physiological and molecular mechanisms of leaf coloring in Acer palmatum, a deciduous tree during autumnal senescence, we first investigated concentration dynamics of pigments (i.e., chlorophyll, carotenoid and anthocyanin) in leaves with differential coloring. It was found that compared to green leaves (GN), anthocyanins were accumulated actively in semi-red (SR) and total-red (TR) leaves, accompanied with chlorophyll and carotenoid degradation. Then transcriptional profiling on GN and SR leaves identified thousands of transcripts with differential expression in SR compared to GN leaves. An annotation search showed that the entire flavonoid/anthocyanin biosynthesis pathway from the production of naringenin chalcone to modification of flavonoid backbone was extensively activated at the transcriptional level in SR leaves. Phylogenetic analysis of putative MYB proteins identified ApMYB1 as a putative regulator promoting anthocyanin biosynthesis. Expression of ApMYB1 in leaves was induced by exogenous hormones including abscisic acid. Stable overexpression of ApMYB1 in tobacco resulted in leaves with higher accumulation of anthocyanins. Collectively, our results identified ApMYB1 as a positive regulator associated with leaf coloring in Acer palmatum during autumnal senescence, which may be regarded a potential target for breeding color-leafed plants.